A multi-element co-doped yttrium aluminum garnet thermal barrier coating material and preparation method thereof
The multinary co-doped yttrium aluminum garnet thermal barrier coating addresses the limitations of YSZ and YAG by enhancing thermal expansion and reducing conductivity, offering improved durability and insulation for high-temperature environments.
Patent Information
- Application Number
- CN202310790086.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-06-30
AI Technical Summary
Existing thermal barrier coatings, such as YSZ and YAG, face issues with high thermal conductivity, low thermal expansion coefficient, and oxygen ion permeability, leading to cracking, peeling, and reduced thermal insulation performance, limiting their application in high-temperature environments.
A multinary co-doped yttrium aluminum garnet (YAG) thermal barrier coating material is developed by doping the Y position with rare earth elements and the Al position with metal elements, resulting in a material with a stable high-temperature phase structure, low oxygen ion permeability, and improved thermal expansion coefficient while maintaining low thermal conductivity.
The co-doped YAG material exhibits excellent comprehensive thermophysical properties, including low thermal conductivity and high thermal expansion coefficient, making it suitable for high-temperature applications with improved durability and insulation performance.
Smart Images

Figure CN116903368B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of thermal barrier coating materials, and in particular relates to the preparation of a multinary co-doped yttrium aluminum garnet ceramic material and the application of the ceramic material as a thermal barrier coating material. Background Art
[0002] Thermal barrier coatings (TBCs) offer excellent thermal insulation and high-temperature oxidation resistance, effectively protecting hot-end components in aerospace, shipbuilding, nuclear industry, automotive, and other fields. They are one of the advanced technologies that can significantly increase engine operating temperatures. Partially stabilized zirconia (YSZ) containing 6-8wt% yttria is a traditional TBC material with a high melting point, high hardness, low thermal conductivity, and a high coefficient of thermal expansion. However, when YSZ is exposed to temperatures above 1200°C, it undergoes a transition from a tetragonal to a monoclinic phase, accompanied by a 3%-5% volume expansion, leading to extensive cracking and flaking of the coating. Furthermore, the high oxygen ion permeability of YSZ accelerates the formation of thermally grown oxides, significantly limiting the service life of YSZ TBCs. Therefore, there is an urgent need to develop TBC materials with high-temperature phase stability and low oxygen ion permeability.
[0003] Yttrium aluminum garnet Y3Al5O 12 YAG (abbreviated as YAG) has become a candidate thermal barrier coating material with great application prospects due to its excellent high temperature phase stability (no phase change before 1970℃) and low oxygen ion permeability (the oxygen diffusion coefficient is one tenth of that of YSZ at the same temperature). However, YAG has a high thermal conductivity (3.2W / m·K, 1000℃) and a low thermal expansion coefficient (9.1×10 -6 K -1 ,1000℃) will lead to the accumulation of thermal stress. When the coating is subjected to thermal expansion or contraction, the thermal stress between it and the substrate material will increase, which may cause the coating to crack or peel off. In addition, the high thermal conductivity makes it easier for heat to be transferred to the substrate material, reducing the thermal insulation performance. In addition, the low thermal expansion coefficient of YAG leads to a mismatch in thermal expansion between the coating and the substrate material. When the temperature changes, the difference in thermal expansion coefficient between the coating and the substrate material will lead to the accumulation of stress, which will eventually lead to cracking or peeling of the coating. In summary, the high thermal conductivity and low thermal expansion coefficient of YAG limit the application of YAG in the field of thermal barrier coatings to a certain extent. Therefore, modifying YAG and improving its thermophysical properties by adjusting its chemical composition and crystal structure is currently the key research direction for the application of YAG as a thermal barrier coating.
[0004] YAG belongs to the cubic crystal system, and its general chemical formula is L3B2(AO4)3 (L, A, B represent dodecahedron, tetrahedron and octahedron respectively). 12 Middle, Y 3+ In the dodecahedral lattice with eight coordination with oxygen ions, Al 3+ In the same 2- The YAG unit cell is considered to be a network of connected dodecahedrons, octahedrons and tetrahedrons, which can be easily replaced by cations with a large ionic radius. For example, Er 3+ Y substituted for the L site of the YAG dodecahedron 3+ , Y2ErAl5O with low thermal conductivity can be obtained 12 ceramics (1.8W / m·K, 1000℃), but its thermal expansion coefficient did not improve and was still 8.63×10 at 1157℃. -6 K -1 Most studies in recent years have shown that the literature on YAG doping modification is based on single element and single point doping, and found that the thermal conductivity is greatly reduced, but the thermal expansion coefficient is almost unchanged, which needs to be further improved.
[0005] Therefore, it is necessary to develop a new thermal barrier coating material with excellent comprehensive thermophysical properties while maintaining low thermal conductivity and high thermal expansion coefficient. Summary of the Invention
[0006] In response to the problems existing in the prior art, the present invention is based on material design for thermal barrier coating applications. One of the purposes is to provide a multinary co-doped yttrium aluminum garnet thermal barrier coating material. The multinary co-doped yttrium aluminum garnet is prepared by doping the Y position of YAG with rare earth elements and the Al position of YAG with metal elements. The multinary co-doped yttrium aluminum garnet has the advantages of stable high-temperature phase structure, low oxygen ion permeability, low thermal conductivity and high thermal expansion coefficient; another purpose of the present invention is to provide a preparation method of the multinary co-doped yttrium aluminum garnet thermal barrier coating material.
[0007] Based on the above purpose, the technical solution adopted by the present invention is as follows:
[0008] In the first aspect, the present invention provides a multi-element co-doped yttrium aluminum garnet thermal barrier coating material, which has a single-phase garnet structure and is prepared by doping the Y position of yttrium aluminum garnet with a rare earth element and doping the Al position of yttrium aluminum garnet with a metal element; the chemical formula of the multi-element co-doped yttrium aluminum garnet thermal barrier coating material is (Y 1- x Ln x )3(Al 1-y B y )5O 12, wherein Ln is at least one of Er, Gd, Sc, Ce, Yb, Nd, Eu, Tb, Lu, Tm, Dy, Ho, La, and Sm; B is at least one of Fe, Mn, Ti, Ca, Mg, Be, Co, Ni, Cu, and Zn; and the doping variables satisfy 0 <x<1,0<y<1。
[0009] The present invention adopts rare earth elements to dope the Y position of yttrium aluminum garnet and metal elements to dope the Al position of yttrium aluminum garnet to form a multi-element co-doped yttrium aluminum garnet thermal barrier coating material, which has a stable high-temperature phase structure, low oxygen ion permeability, and improves the thermal expansion coefficient while maintaining low thermal conductivity. It is a candidate thermal barrier coating material with excellent comprehensive thermophysical properties and broad application prospects.
[0010] Preferably, the chemical formula of the multi-element co-doped yttrium aluminum garnet thermal barrier coating material (Y 1-x Ln x )3(Al 1-y B y )5O 12 One of the following conditions is met:
[0011] (a) When Ln is Er and B is Fe, the doping variables satisfy x = 0.6, 0.4 ≤ y ≤ 0.8;
[0012] (b) When Ln is Er and B is Mn, the doping variables satisfy x = 0.6, 0.04 ≤ y ≤ 0.1;
[0013] (c) When Ln is Er and B is Ti, the doping variables satisfy x=0.6, 0.04≤y≤0.1.
[0014] Preferably, the chemical formula of the multi-element co-doped yttrium aluminum garnet thermal barrier coating material (Y 1-x Ln x )3(Al 1-y B y )5O 12 One of the following conditions is met:
[0015] (a) When Ln is Er and B is Fe, the doping variables satisfy x = 0.6, 0.6 ≤ y ≤ 0.8;
[0016] (b) When Ln is Er and B is Mn, the doping variables satisfy x = 0.6, 0.06 ≤ y ≤ 0.1;
[0017] (c) When Ln is Er and B is Ti, the doping variables satisfy x=0.6, 0.08≤y≤0.1.
[0018] Experiments have shown that when the above condition (a) is met, the thermal conductivity of the multi-element co-doped yttrium aluminum garnet thermal barrier coating material is as low as 1.31 W / m·k at 1100°C, and the thermal expansion coefficient is as high as 11×10 -6 K -1 When the above condition (b) is met, the thermal conductivity of the multi-element co-doped yttrium aluminum garnet thermal barrier coating material is as low as 1.38W / m·k at 1100℃, and the thermal expansion coefficient is as high as 9.05×10 -6 K -1 When the above condition (c) is met, the thermal conductivity of the multi-element co-doped yttrium aluminum garnet thermal barrier coating material is as low as 1.41W / m·k at 1100℃, and the thermal expansion coefficient is as high as 9.08×10 -6 K -1 .
[0019] In a second aspect, the present invention provides a method for preparing the above-mentioned multi-element co-doped yttrium aluminum garnet thermal barrier coating material, comprising the following steps:
[0020] S1: respectively subjecting Y2O3 powder, Al(OH)3 powder, rare earth element compound powder or metal element compound powder to a first ball milling or sand milling until the particle size reaches nanometer level, and drying to obtain nanometer-level powder Y2O3, Al(OH)3, rare earth element compound or metal element compound;
[0021] S2: ball milling the nano-sized powders of Y2O3, Al(OH)3, rare earth element compounds and metal element compounds for a second time, drying them, grinding and screening them, and then sintering the powders to obtain a powder material of yttrium aluminum garnet co-doped with rare earth elements and metal elements;
[0022] S3: The powder material of yttrium aluminum garnet co-doped with rare earth elements and metal elements obtained in step S2 is ball-milled for the third time, dried, ground and sieved, the sieved powder is pressed into a block, and the block is sintered to obtain a multi-element co-doped yttrium aluminum garnet thermal barrier coating material.
[0023] The present invention adopts a ceramic preparation method that combines "ball milling + sand milling + secondary ball milling + grinding + sintering + tertiary ball milling + grinding + sintering". The nano-scale powder obtained by the first ball milling and sand milling is subjected to a second ball milling, drying, grinding and screening, and phase sintering, and then a third ball milling, drying, grinding and screening, and ceramic sintering is performed. The prepared ceramic material has higher phase purity, smaller grain size, more uniform component distribution, and the doped ions are more easily fully dissolved in the YAG lattice. This is because the particle size of the nano-scale raw material powder is uniform and fine, which is more conducive to powder phase formation; after the nano-scale powder is ball-milled, dried, ground and screened, and sintered for the second time, it is ball-milled, dried, ground and screened, and ceramic sintered for the third time, so that the particle size of the sintered ceramic grains is further refined and uniform, the phase formation is more complete, and the mixing uniformity is better, thereby developing a multi-element co-doped yttrium aluminum garnet thermal barrier coating ceramic material with a single YAG phase, stable high-temperature phase structure, precise doping ion ratio, controllable doping ion occupancy, low oxygen ion permeability, and excellent comprehensive thermal physical properties, which solves the shortcomings of existing thermal barrier coating materials such as poor high-temperature phase stability, high oxygen ion permeability, excessively high thermal conductivity, and too low thermal expansion coefficient. The multi-element co-doped yttrium aluminum garnet thermal barrier coating ceramic material prepared by the method of the present invention can be applied to aerospace, shipbuilding, nuclear industry, automobile and other fields, providing a new thermal barrier coating material for hot end components such as aircraft engines, ground gas turbines, solid fuel engines, etc., has broad application prospects and huge market demand, and can bring significant economic and social benefits.
[0024] Preferably, the chemical formula of the multi-element co-doped yttrium aluminum garnet thermal barrier coating material is (Y 1-x Ln x )3(Al 1-y B y )5O 12 , wherein Ln is at least one of Er, Gd, Sc, Ce, Yb, Nd, Eu, Tb, Lu, Tm, Dy, Ho, La, and Sm; B is at least one of Fe, Mn, Ti, Ca, Mg, Be, Co, Ni, Cu, and Zn; and the doping variables satisfy 0 <x<1,0<y<1。
[0025] Preferably, the chemical formula of the multi-element co-doped yttrium aluminum garnet thermal barrier coating material (Y 1-x Ln x )3(Al 1-y B y )5O 12 One of the following conditions is met:
[0026] (a) When Ln is Er and B is Fe, the doping variables satisfy x = 0.6, 0.4 ≤ y ≤ 0.8;
[0027] (b) When Ln is Er and B is Mn, the doping variables satisfy x = 0.6, 0.04 ≤ y ≤ 0.1;
[0028] (c) When Ln is Er and B is Ti, the doping variables satisfy x=0.6, 0.04≤y≤0.1.
[0029] Preferably, the chemical formula of the multi-element co-doped yttrium aluminum garnet thermal barrier coating material (Y 1-x Ln x )3(Al 1-y B y )5O 12 One of the following conditions is met:
[0030] (a) When Ln is Er and B is Fe, the doping variables satisfy x = 0.6, 0.6 ≤ y ≤ 0.8;
[0031] (b) When Ln is Er and B is Mn, the doping variables satisfy x = 0.6, 0.06 ≤ y ≤ 0.1;
[0032] (c) When Ln is Er and B is Ti, the doping variables satisfy x=0.6, 0.08≤y≤0.1.
[0033] Preferably, the rare earth element compound is at least one of Er2O3, Gd2O3, Sc2O3, CeO2, Yb2O3, Nd2O3, Eu2O3, Tb2O3, Lu2O3, Tm2O3, Dy2O3, Ho2O3, La2O3, and Sm2O3; and the metal element compound is at least one of TiO2, Fe2O3, MnCO3, CaCO3, MgO, BeO, CoO, NiO, CuO, and ZnO.
[0034] The present invention designs materials based on the application of thermal barrier coatings. In order to precisely control the doping position, the cation radius and Y 3+ Similar rare earth oxides Er2O3, Gd2O3, Sc2O3, CeO2, Yb2O3, Nd2O3, Eu2O3, Tb2O3, Lu2O3, Tm2O3, Dy2O3, Ho2O3, La2O3 or Sm2O3 have a great influence on the performance of Y3Al5O 12 On the basis of rare earth element doping Y position, the cation radius is much smaller than Y 3+ And slightly larger than Al 3+ The three metal element compounds TiO2, Fe2O3, MnCO3 and the compounds with divalent cations CaCO3, MgO, BeO, CoO, NiO, CuO, ZnO have an effect on the Y3Al5O 12By doping Al in the middle position, a multinary co-doped yttrium aluminum garnet ceramic material was prepared by solid-phase synthesis. This multinary co-doped yttrium aluminum garnet thermal barrier coating material is a promising candidate for thermal barrier coatings with excellent comprehensive thermophysical properties and a wide range of applications.
[0035] Preferably, the rotation speed of the first ball milling, the second ball milling and the third ball milling is 150 r / min, and the ball milling time is 24 hours; in steps S1 to S3, the drying temperature is 80° C. to 90° C. and the drying time is 24 hours.
[0036] Preferably, the sieving in step S2 is through an 80-mesh sieve, and the sieving in step S3 is through a 200-mesh sieve.
[0037] Preferably, the pressing and forming into a block in step S3 includes the following steps:
[0038] The sieved powder was pre-pressed at 8 MPa for 50-60 seconds, and cold isostatically pressed at 220 MPa under vacuum conditions for 90-180 seconds to obtain a block.
[0039] Preferably, the temperature conditions for sintering the powder phase in step S2 are as follows: heating to 1000°C at 5°C / min, then heating to 1300°C at 2°C / min, keeping at 1000°C to 1600°C for 3 to 10 hours, and then cooling to room temperature at 100°C / h;
[0040] The temperature conditions for sintering the block in step S3 are as follows: heating to 1000°C at 5°C / min, then heating to 1300°C at 2°C / min, keeping at 1000°C-1600°C for 3-10 hours, and then cooling to room temperature at 100°C / h.
[0041] Preferably, the preparation method of the nano-powder Y2O3, Al(OH)3, rare earth oxide or metal oxide in step S1 is as follows:
[0042] Water and polymethacrylic acid amine dispersant were added to Y2O3 powder, Al(OH)3 powder, rare earth element compound powder or metal element compound powder respectively, and the mixture was ball-milled at 150 r / min for 24 h, and then sand-milled at 2300 r / min, 2500 r / min and 2700 r / min for 1 h respectively. After drying, Y2O3 nano-powder, Al(OH)3 nano-powder, rare earth oxide nano-powder or metal oxide nano-powder was obtained respectively.
[0043] Preferably, during the ball milling process, the weight ratio of Y2O3 powder, rare earth element compound powder and water is 1:1.5. When the solid content of Y2O3 powder and rare earth element compound powder is less than 40%, 4wt‰ of polymethacrylic acid amine dispersant is added to Y2O3 powder and rare earth element compound powder respectively; the weight ratio of Al(OH)3 powder and metal element compound powder and water is 1:4. When the solid content of Al(OH)3 powder is less than 20%, 2wt% of polymethacrylic acid amine dispersant is added to Al(OH)3 powder; when the solid content of metal element compound powder is less than 20% to 30%, 1 to 2wt% of polymethacrylic acid amine dispersant is added to the metal element compound powder;
[0044] Preferably, when the solid content of the metal element compound MnCO3 powder is less than 20%, 2 wt% of polymethacrylic acid amine dispersant is added thereto; when the solid content of the metal element compound Fe2O3 and TiO2 is less than 30%, 1 wt% of polymethacrylic acid amine dispersant is added thereto;
[0045] During the sand grinding process, when the Y2O3 powder, Al(OH)3 powder, rare earth element compound powder or metal element compound powder becomes viscous, 1 g of polymethacrylate dispersant is added to the powder; when a large number of bubbles appear in the powder, 2 drops of n-octanol are added to the powder.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] (1) The present invention utilizes rare earth elements doped at the Y site of yttrium aluminum garnet and metal elements doped at the Al site of yttrium aluminum garnet to produce a multinary co-doped yttrium aluminum garnet thermal barrier coating material. Through material design, the YAG material maintains its original excellent properties, such as good high-temperature phase stability and low oxygen ion permeability, while also reducing thermal conductivity and increasing thermal expansion coefficient, thereby improving its overall thermophysical properties. This makes it a candidate thermal barrier coating material with excellent comprehensive thermophysical properties, and has broad application prospects in aerospace, shipbuilding, nuclear industry, automotive, and other fields.
[0048] (2) The present invention adopts a ceramic preparation method that combines "ball milling + sand milling + secondary ball milling + grinding + sintering + tertiary ball milling + grinding + sintering". The nano-scale raw material powder obtained by ball milling and sand milling is subjected to secondary ball milling, grinding and screening, and phase sintering, and then ball milling, grinding and screening, and ceramic sintering are performed three times. The prepared ceramic material has higher physical phase purity, smaller grain size, and more uniform component distribution. The doped ions are more easily fully dissolved in the YAG lattice, so that the prepared multi-element co-doped yttrium aluminum garnet thermal barrier coating ceramic material has a single YAG phase, a stable high-temperature phase structure, a precise doped ion ratio, controllable doped ion occupancy, and a low oxygen ion transmittance. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] To better illustrate the objectives, technical solutions, and advantages of the present invention, the present invention will be further described below with reference to specific examples. Those skilled in the art will appreciate that the specific examples described herein are intended only to illustrate the present invention and are not intended to limit the present invention. The experimental methods used in the examples are conventional methods unless otherwise specified; the materials and reagents used are commercially available unless otherwise specified.
[0050] Figure 1 This is a flow chart for preparing the multi-element co-doped yttrium aluminum garnet thermal barrier coating material of Examples 1 to 5;
[0051] Figure 2 This is the XRD pattern of the ceramic material obtained in Example 1;
[0052] Figure 3 This is the SEM-EDS image of the ceramic material obtained in Example 1;
[0053] Figure 4 This is a graph of the thermal conductivity of the ceramic material obtained in Example 1;
[0054] Figure 5 The average thermal expansion coefficient diagram of the ceramic material obtained in Example 1;
[0055] Figure 6 Thermal conductivity diagram of the ceramic material obtained in Example 2;
[0056] Figure 7 The average thermal expansion coefficient diagram of the ceramic material obtained in Example 2;
[0057] Figure 8 This is a graph of the thermal conductivity of the ceramic material obtained in Example 3;
[0058] Figure 9 The average thermal expansion coefficient diagram of the ceramic material obtained in Example 3;
[0059] Figure 10 Thermal conductivity graphs of ceramic materials obtained for Examples 4 and 5;
[0060] Figure 11 The average thermal expansion coefficient of the ceramic materials prepared in Examples 4 and 5 is shown. DETAILED DESCRIPTION
[0061] Example 1
[0062] In this embodiment, a solid phase synthesis method is used to prepare a YAG thermal barrier coating material co-doped with rare earth element Er and metal element Fe. The preparation method is as follows: Figure 1 As shown, the following steps are included:
[0063] S1: Preparation of nanopowder raw materials Y2O3, Er2O3, Al(OH)3, Fe2O3
[0064] Deionized water and a polymethacrylamide dispersant (CE64) were added to 99.999wt% pure Y2O3 powder, 99.99wt% pure Er2O3 powder, analytically pure Al(OH)3 powder, and 99.99wt% pure Fe2O3 powder, respectively. The mixture was then placed in a polyurethane ball mill for the first round of ball milling. The Y2O3 powder-to-water ratio was 1:1.5; the Er2O3 powder-to-water ratio was 1:1.5; the Al(OH)3 powder-to-water ratio was 1:4; and the Fe2O3 powder-to-water ratio was 3:7. The polyurethane ball mill was then placed in a planetary ball mill and milled at 150 rpm for 24 hours. When ball-milling Y2O3 powder and Er2O3 powder, when their solid content is less than 40%, add 4wt‰ of CE64 dispersant thereto; when ball-milling Al(OH)3 powder, when its solid content is less than 20%, add 2wt% of CE64 dispersant thereto; when ball-milling Fe2O3 powder, when its solid content is less than 30%, add 1wt% of CE64 dispersant thereto.
[0065] The slurry was then poured into a sand mill and sand-milled for 1 hour at speeds of 2300, 2500, and 2700 r / min, respectively. Simultaneously, a polymethacrylamide dispersant (CE64) was added dropwise according to the proportions: 4 wt% of dispersant was added to the Y2O3 and Er2O3 powders; 2 wt% of dispersant was added to the Al(OH)3 powder; and 1 wt% of dispersant was added to the Fe2O3 powder. After sand-milling, the slurry was poured into a stainless steel tray and dried in an oven at 90°C for 24 hours to obtain a nanopowder with uniform particle size.
[0066] During the sand grinding process, if the powder material is sticky, 1g of polymethacrylamide dispersant needs to be added to the powder material. This is because the surface interaction between the particles of the powder during the sand grinding process causes it to easily agglomerate and have poor fluidity. At the same time, the sand grinding process is relatively long. Adding a dispersant to the slurry can effectively improve the sand grinding efficiency and fully break up the interaction between the powders during the sand grinding process, so that the ground powder will not agglomerate and has good fluidity. If there are a lot of bubbles during sand grinding, 2 drops of n-octanol can be added. This is because n-octanol can improve the coating properties and curb or reduce the generation of bubbles from the source.
[0067] S2: Mixing of nanopowder raw materials, second ball milling and drying, grinding and screening, and sintering to prepare multi-element co-doped yttrium aluminum garnet powder material
[0068] Y2O3, Er2O3, Al(OH)3, Fe2O3 nanopowders were prepared according to the chemical formula ((Y0.4 Er 0.6 )3(Al 1-y Fe y )5O 12 , y = 0.2, 0.4, 0.6, 0.8) were weighed and mixed, and anhydrous ethanol was added to the mixture as a dispersant. The mass ratio of the dispersant to the nano-powder mixture was 2:1. Among them, when y=0.2, the molar ratio of Y2O3, Er2O3, Al(OH)3, and Fe2O3 powders is 0.6:0.9:4:0.5; when y=0.4, the molar ratio of Y2O3, Er2O3, Al(OH)3, and Fe2O3 powders is 0.6:0.9:3:1; when y=0.6, the molar ratio of Y2O3, Er2O3, Al(OH)3, and Fe2O3 powders is 0.6:0.9:2:1.5; when y=0.8, the molar ratio of Y2O3, Er2O3, Al(OH)3, and Fe2O3 powders is 0.6:0.9:1:2.
[0069] The materials mixed according to the stoichiometric ratio of different chemical formulas were poured into nylon ball mill jars and placed in a planetary ball mill for a second ball milling at 150r / min for 24h. After the ball milling was completed, the materials were poured into a beaker, the beaker mouth was sealed with a film, a few small holes were poked with a knife, and the mixture was placed in an electric constant temperature blast drying oven at a constant temperature of 80℃ for 24h; the dried nano-scale powder mixture was ground with an agate mortar and passed through an 80-mesh sieve, poured into a crucible after screening, and then placed in a box-type resistance furnace set at 1300℃ for 3h to sinter the powder phase, wherein the heating rate was 5℃ / min below 1000℃ and 2℃ / min above 1000℃; after sintering, the temperature was lowered to room temperature at 100℃ / h to obtain a product with the chemical formula (Y 0.4 Er 0.6 )3(Al 1-y Fe y )5O 12 , powder materials with y=0.2, 0.4, 0.6, and 0.8.
[0070] S3: The powder material obtained by sintering in step S2 is dried by ball milling for the third time, ground and screened, pressed into tablets and sintered to prepare a multi-element co-doped yttrium aluminum garnet ceramic material.
[0071] The powder materials obtained by sintering in step S2 were poured into nylon ball mill jars and placed in a planetary ball mill, and ball milled for the third time at 150 r / min for 24 h. After ball milling, they were placed in an electric constant temperature blast drying oven at a constant temperature of 80°C and dried for 24 h. Then, they were ground with an agate mortar and passed through a 200-mesh sieve. The sieved powder materials were pressed into tablets (after sintering, the diameter must meet 12.7 mm and the thickness must be 1-3 mm) or strips (after sintering, the thickness must meet 12.7 mm). After the pressing is completed, the sheet is wrapped with plastic film, placed in a vacuum bag and evacuated, and cold isostatic pressing is performed at 220 MPa, with the pressure maintained for 90 seconds. The pressed block is sent to a resistance furnace and set at 1300°C for 8 hours for secondary sintering, wherein the heating rate is 5°C / min below 1000°C and 2°C / min above 1000°C; after sintering, the temperature is lowered to room temperature at 100°C / h, and the chemical formula is finally obtained (Y 0.4 Er 0.6 )3(Al 1-y Fe y )5O 12 , the ceramic materials with y=0.2, 0.4, 0.6, and 0.8 are the multinary co-doped yttrium aluminum garnet thermal barrier coating materials of the present invention.
[0072] Performance testing
[0073] (1) XRD test
[0074] The chemical formula prepared in Example 1 is (Y 0.4 Er 0.6 )3(Al 1-y Fe y )5O 12 , XRD test was performed on ceramic materials with y=0.2, 0.4, 0.6, and 0.8, such as Figure 2 As shown in FIG, the ceramic material has a single garnet structure, indicating that Er and Fe are completely dissolved in the YAG lattice.
[0075] (3) SEM-EDS scanning
[0076] The (Y 0.4 Er 0.6 )3(Al 0.4 Fe 0.6 )5O 12 SEM-EDS scanning of ceramic materials, such as Figure 3 As shown, the ceramic material has no impurity phase, uniform grain size, clear grain boundaries, low porosity and good density; the elements are evenly distributed, there is no element segregation or accumulation, and the mixing uniformity is good.
[0077] (4) Thermal conductivity test
[0078] The (Y 0.4 Er 0.6 )3(Al 1-y Fe y )5O 12 , thermal conductivity tests were conducted on ceramic materials with y = 0.2, 0.4, 0.6, and 0.8, such as Figure 4 As shown in the figure, at 1100℃, with the increase of Fe doping amount, (Y 0.4 Er 0.6 )3(Al 1-y Fe y )5O 12 The thermal conductivity of ceramic materials shows a process of first increasing and then decreasing, where the chemical formula is (Y 0.4 Er 0.6 )3(Al 0.2 Fe 0.8 )5O 12 The thermal conductivity of ceramic materials is the lowest, which is 1.31W / m·K.
[0079] (5) Thermal expansion performance test
[0080] The (Y 0.4 Er 0.6 )3(Al 1-y Fe y )5O 12 , thermal expansion performance test of ceramic materials with y=0.2, 0.4, 0.6, and 0.8, such as Figure 5 As shown in the figure, with the increase of Fe doping amount, (Y 0.4 Er 0.6 )3(Al 1-y Fe y )5O 12 The average thermal expansion coefficient of ceramic materials gradually increases, where the chemical formula is (Y 0.4 Er 0.6 )3(Al 0.2 Fe 0.8 )5O 12 The thermal expansion coefficient of ceramic materials is the highest, which is 10.2×10 -6 K -1 .
[0081] Example 2
[0082] In this embodiment, a yttrium aluminum garnet thermal barrier coating material co-doped with rare earth element Er and metal element Mn is prepared by a solid phase synthesis method. The preparation method includes the following steps:
[0083] S1: Preparation of nanopowder raw materials Y2O3, Er2O3, Al(OH)3, and MnCO3
[0084] Y2O3 powder (99.999wt%), Er2O3 powder (99.99wt%), analytically pure Al(OH)3 powder, MnCO3 powder (99.99wt%), deionized water, and a polymethacrylic acid amine dispersant were placed in a polyurethane ball mill according to the appropriate ratios for the initial milling. The Y2O3 powder-to-water ratio was 1:1.5; the Er2O3 powder-to-water ratio was 1:1.5; and the Al(OH)3 and MnCO3 powder-to-water ratios were 1:4. The polyurethane ball mill was placed in a planetary ball mill and milled at 150 rpm for 24 hours. When ball-milling Y2O3 powder and Er2O3 powder, when their solid content is less than 40%, add 4wt‰ of CE64 dispersant thereto; when ball-milling Al(OH)3 and MnCO3 powder, when their solid content is less than 20%, add 2wt% of CE64 dispersant thereto.
[0085] The slurry was then poured into a sand mill and sand-milled for 1 hour at speeds of 2300, 2500, and 2700 rpm, respectively. Simultaneously, a polymethacrylamide dispersant was added dropwise according to the appropriate ratio: 4 wt% of dispersant was added to the Y2O3 and Er2O3 powders, and 2 wt% of dispersant was added to the Al(OH)3 and MnCO3 powders. After sand-milling, the slurry was poured into a stainless steel tray and dried in an oven at 90°C for 24 hours to obtain a nanopowder with uniform particle size.
[0086] S2: Mixing of nanopowder raw materials, second ball milling and drying, grinding and screening, and sintering to prepare multi-element co-doped yttrium aluminum garnet powder material
[0087] Y2O3, Er2O3, Al(OH)3, MnCO3 nanopowders were prepared according to the chemical formula ((Y 0.4 Er 0.6 )3(Al 1-y Mn y )5O 12Materials were weighed and mixed in a stoichiometric ratio of y = 0.02, 0.04, 0.06, 0.08, and 0.1, and anhydrous ethanol was added to the mixture as a dispersant. The mass ratio of the dispersant to the nano-powder mixture was 2:1. Among them, when y=0.02, the molar ratio of Y2O3, Er2O3, Al(OH)3, and MnCO3 powders is 0.6:0.9:4.9:0.1; when y=0.04, the molar ratio of Y2O3, Er2O3, Al(OH)3, and MnCO3 powders is 0.6:0.9:4.8:0.2; when y=0.06, the molar ratio of Y2O3, Er2O3, Al(OH)3, and MnCO3 powders is 0.6:0.9:4.7:0.3; when y=0.08, the molar ratio of Y2O3, Er2O3, Al(OH)3, and MnCO3 powders is 0.6:0.9:4.6:0.4; when y=0.1, the molar ratio of each powder is 0.6:0.9:4.5:0.5.
[0088] The materials mixed according to the stoichiometric ratio of different chemical formulas were poured into nylon ball mill jars and placed in a planetary ball mill for a second ball milling at 150r / min for 24h. After the ball milling was completed, the materials were poured into a beaker, the beaker mouth was sealed with a film, a few small holes were poked with a knife, and the materials were placed in an electric constant temperature blast drying oven at a constant temperature of 80℃ for 24h; the dried materials were ground with an agate mortar and passed through an 80-mesh sieve, and after screening, they were poured into a crucible, and then placed in a box-type resistance furnace set at 1300℃ for 3h to perform powder phase sintering, wherein the heating rate was 5℃ / min below 1000℃ and 2℃ / min above 1000℃; after sintering, the temperature was lowered to room temperature at 100℃ / h to obtain a chemical formula (Y 0.4 Er 0.6 )3(Al 1-y Mn y )5O 12 , powder materials with y=0.02, 0.04, 0.06, 0.08, and 0.1.
[0089] S3: The powder material obtained by sintering in step S2 is dried by ball milling for the third time, ground and screened, pressed into tablets and sintered to prepare a multi-element co-doped yttrium aluminum garnet ceramic material.
[0090] The dispersant anhydrous ethanol was added to the powder material obtained by sintering in step S2, and the mass ratio of the powder material to the anhydrous ethanol was 1:2. The powder material with the dispersant was poured into a nylon ball mill and placed in a planetary ball mill. The third ball milling was carried out at 150 r / min for 24 h. After the ball milling, it was placed in an electric constant temperature blast drying oven at a constant temperature of 80 ° C and dried for 24 h; then the powder material was ground with an agate mortar and passed through a 200 mesh sieve. The sieved powder material was pressed on a tablet press. 8MPa pre-pressing molding, holding pressure for 50s; after the tableting is completed, the tablet is wrapped with plastic film, placed in a vacuum bag, and vacuumed, and cold isostatic pressing is performed at 220MPa, holding pressure for 90s. The pressed block is sent to a resistance furnace and set at 1300℃ for 8h for secondary sintering, wherein the heating rate is 5℃ / min below 1000℃ and 2℃ / min above 1000℃; after sintering, the temperature is lowered to room temperature at 100℃ / h, and the chemical formula is finally obtained (Y 0.4 Er 0.6 )3(Al 1-y Mn y )5O 12 , the multinary co-doped yttrium aluminum garnet ceramic material with y=0.02, 0.04, 0.06, 0.08, and 0.1 is the multinary co-doped yttrium aluminum garnet thermal barrier coating material of the present invention.
[0091] Performance testing
[0092] (1) Thermal conductivity test
[0093] The (Y 0.4 Er 0.6 )3(Al 1-y Mn y )5O 12 , thermal conductivity tests were conducted on ceramic materials with y=0.02, 0.04, 0.06, 0.08, and 0.1, such as Figure 6 As shown in the figure, at 1100℃, with the increase of Mn doping amount, (Y 0.4 Er 0.6 )3(Al 1- y Mn y )5O 12 The thermal conductivity of ceramic materials shows a process of first decreasing and then increasing, where the chemical formula is (Y 0.4 Er 0.6 )3(Al 0.94 Mn 0.06 )5O 12 The thermal conductivity of ceramic materials is the lowest, which is 1.38W / m·K.
[0094] (2) Thermal expansion performance test
[0095] The (Y 0.4 Er 0.6 )3(Al 1-y Mn y )5O 12 , thermal expansion performance test of ceramic materials with y=0.02, 0.04, 0.06, 0.08, and 0.1, such as Figure 7 As shown in the figure, with the increase of Mn doping amount, (Y 0.4 Er 0.6 )3(Al 1-y Mn y )5O 12 The average thermal expansion coefficient of ceramic materials continues to increase, and the chemical formula is (Y 0.4 Er 0.6 )3(Al 0.9 Mn 0.1 )5O 12 The thermal expansion coefficient of ceramic materials is the highest, which is 9.05×10 -6 K -1 .
[0096] Example 3
[0097] This embodiment uses a solid-phase synthesis method to prepare a yttrium aluminum garnet thermal barrier coating material co-doped with the rare earth element Er and the metal element Ti, which specifically includes the following steps:
[0098] S1: Preparation of nano-scale powder raw materials Y2O3, Er2O3, Al(OH)3, and TiO2
[0099] 99.999wt% pure Y2O3, 99.99wt% pure Er2O3, analytically pure Al(OH)3, 99.99wt% pure TiO2, deionized water, and a polymethacrylamide dispersant were poured into a polyurethane ball mill for the first round of ball milling. The mass ratio of Y2O3 powder to water was 1:1.5; the mass ratio of Er2O3 powder to water was 1:1.5; the mass ratio of Al(OH)3 powder to water was 1:4; and the mass ratio of TiO2 powder to water was 3:7. The polyurethane ball mill was placed in a planetary ball mill and milled at 150 rpm for 24 hours. When ball-milling Y2O3 powder and Er2O3 powder, when their solid content is less than 40%, add 4wt‰ of CE64 dispersant thereto; when ball-milling Al(OH)3 powder, when its solid content is less than 20%, add 2wt% of CE64 dispersant thereto; when ball-milling TiO2 powder, when its solid content is less than 30%, add 1wt% of CE64 dispersant thereto.
[0100] The slurry was then poured into a sand mill and sand-milled for 1 hour at speeds of 2300, 2500, and 2700 r / min, respectively. Simultaneously, polymethacrylamide dispersant was added dropwise according to the proportions: 4 wt% polymethacrylamide dispersant was added to the Y2O3 and Er2O3 powders; 2 wt% polymethacrylamide dispersant was added to the Al(OH)3 powder; and 1 wt% polymethacrylamide dispersant was added to the TiO2 powder. After sand-milling, the slurry was poured into a stainless steel tray and dried in an oven at 90°C for 24 hours to obtain a nanopowder with uniform particle size.
[0101] S2: Mixing of nano-scale powder raw materials, secondary ball milling and drying, grinding, screening and sintering to prepare multi-element co-doped yttrium aluminum garnet powder material
[0102] Y2O3, Er2O3, Al(OH)3, TiO2 nanopowders were prepared according to the chemical formula ((Y 0.4 Er 0.6 )3(Al 1-y Ti y )5O 12 Materials were weighed and mixed in a stoichiometric ratio of y = 0.02, 0.04, 0.06, 0.08, and 0.1, and anhydrous ethanol was added to the mixture as a dispersant. The mass ratio of the dispersant to the nano-powder mixture was 2:1. Among them, when y=0.02, the molar ratio of Y2O3, Er2O3, Al(OH)3 and TiO2 powders is 0.6:0.9:4.9:0.1; when y=0.04, the molar ratio of Y2O3, Er2O3, Al(OH)3 and TiO2 powders is 0.6:0.9:4.8:0.2; when y=0.06, the molar ratio of Y2O3, Er2O3, Al(OH)3 and TiO2 powders is 0.6:0.9:4.7:0.3; when y=0.08, the molar ratio of Y2O3, Er2O3, Al(OH)3 and TiO2 powders is 0.6:0.9:4.6:0.4; when y=0.1, the molar ratio of each powder is 0.6:0.9:4.5:0.5.
[0103] The materials mixed according to the stoichiometric ratio of different chemical formulas were poured into nylon ball mill jars and placed in a planetary ball mill for a second ball milling at 150r / min for 24h. After the ball milling was completed, the materials were poured into a beaker, the beaker mouth was sealed with a film, a few small holes were poked with a knife, and the mixture was placed in an electric constant temperature blast drying oven at a constant temperature of 80℃ for 24h; the dried nano-scale powder mixture was ground with an agate mortar and passed through an 80-mesh sieve, poured into a crucible after screening, and then placed in a box-type resistance furnace set at 1300℃ for 3h to sinter the powder phase, wherein the heating rate was 5℃ / min below 1000℃ and 2℃ / min above 1000℃; after sintering, the temperature was cooled to room temperature at 100℃ / h to obtain a chemical formula of (Y 0.4 Er 0.6 )3(Al 1-y Ti y )5O 12 , powder materials with y=0.02, 0.04, 0.06, 0.08, and 0.1.
[0104] S3: The powder material obtained by sintering in step S2 is dried by ball milling for the third time, ground and screened, pressed into tablets and sintered to prepare a multi-element co-doped yttrium aluminum garnet ceramic material.
[0105] The powder materials obtained in step S2 were poured into nylon ball mill jars and placed in a planetary ball mill, and ball milled for the third time at 150 r / min for 24 h. After ball milling, the powder materials were placed in an electric constant temperature blast drying oven at a constant temperature of 80°C for 24 h. Then, the powder materials were ground with an agate mortar and passed through a 200-mesh sieve. The sieved powder materials were pre-pressed at 8 MPa on a tablet press, and the pressure was maintained for 50 s. After the tableting was completed, the tablets were wrapped with plastic film, placed in a vacuum bag and evacuated, and cold isostatically pressed at 220 MPa for 90 s. The pressed blocks were sent to a resistance furnace and set to 1300°C for 8 h for secondary sintering, wherein the heating rate was 5°C / min below 1000°C and 2°C / min above 1000°C. After sintering, the temperature was cooled to room temperature at 100°C / h, and the chemical formula was finally obtained. (Y 0.4 Er 0.6 )3(Al 1-y Ti y )5O 12 , the ceramic materials with y=0.02, 0.04, 0.06, 0.08, and 0.1 are the multi-element co-doped yttrium aluminum garnet thermal barrier coating materials of the present invention.
[0106] Performance testing
[0107] (1) Thermal conductivity test
[0108] The (Y 0.4 Er 0.6 )3(Al 1-yTi y )5O 12 , thermal conductivity tests were conducted on ceramic materials with y=0.02, 0.04, 0.06, 0.08, and 0.1, such as Figure 8 As shown in the figure, with the increase of Ti doping amount, at 1100℃, (Y 0.4 Er 0.6 )3(Al 1- y Ti y )5O 12 The thermal conductivity of ceramic materials shows a process of first decreasing and then increasing, where the chemical formula is (Y 0.4 Er 0.6 )3(Al 0.92 Ti 0.08 )5O 12 The thermal conductivity of ceramic materials is the lowest, which is 1.41W / m·K.
[0109] (2) Thermal expansion performance test
[0110] The (Y 0.4 Er 0.6 )3(Al 1-y Ti y )5O 12 , thermal expansion performance test of ceramic materials with y=0.02, 0.04, 0.06, 0.08, and 0.1, such as Figure 9 As shown in the figure, with the increase of Ti doping amount, (Y 0.4 Er 0.6 )3(Al 1-y Ti y )5O 12 The average thermal expansion coefficient of ceramic materials decreases first and then increases, where the chemical formula is (Y 0.4 Er 0.6 )3(Al 0.98 Ti 0.02 )5O 12 The thermal expansion coefficient of ceramic materials is the highest, which is 9.08×10 -6 K -1 .
[0111] Example 4
[0112] In this embodiment, a solid-phase synthesis method is used to prepare a yttrium aluminum garnet thermal barrier coating material co-doped with the rare earth element Er and the metal element Ca. The specific preparation method includes the following steps:
[0113] S1: Preparation of nano-scale powder raw materials
[0114] 99.999wt% pure Y2O3 powder, 99.99wt% Er2O3 powder, analytically pure Al(OH)3 powder, 99.99wt% CaCO3 powder, deionized water, and polymethacrylamide dispersant were placed in a polyurethane ball mill for the first round of ball milling. The mass ratio of Y2O3 powder to water was 1:1.5; the mass ratio of Er2O3 powder to water was 1:1.5; and the mass ratio of Al(OH)3 powder and CaCO3 powder to water was 1:4. The polyurethane ball mill was placed in a planetary ball mill and milled at 150 rpm for 24 hours. When the solids content of the Y2O3 and Er2O3 powders was less than 40%, 4wt‰ of CE64 dispersant was added. When the solids content of the Al(OH)3 and CaCO3 powders was less than 20%, 2wt% of CE64 dispersant was added.
[0115] The slurry was then poured into a sand mill and sand-milled for 1 hour at speeds of 2300, 2500, and 2700 rpm, respectively. Simultaneously, a polymethacrylamide dispersant was added dropwise according to the appropriate ratio: 4 wt% of dispersant was added to the Y2O3 and Er2O3 powders, and 2 wt% of dispersant was added to the Al(OH)3 and CaCO3 powders. After sand-milling, the slurry was poured into a stainless steel tray and dried in an oven at 90°C for 24 hours to obtain a nanopowder with uniform particle size.
[0116] S2: Mixing of nano-scale powder raw materials, secondary ball milling and drying, grinding, screening and sintering to prepare multi-element co-doped yttrium aluminum garnet powder material
[0117] Mix Y2O3, Er2O3, Al(OH)3, and CaCO3 nanopowders in a molar ratio of 6:9:47.5:2.5. Add anhydrous ethanol as a dispersant, with a mass ratio of dispersant to nanopowder mixture of 2:1. Pour the mixture into a nylon milling jar and place it in a planetary ball mill for a second milling at 150 rpm for 24 hours. After the ball milling is completed, the material is poured into a beaker, the beaker mouth is sealed with a film, a few small holes are poked with a knife, and the material is placed in an electric constant temperature blast drying oven at a constant temperature of 80°C for 24 hours; the dried nano-scale mixture is ground with an agate mortar and passed through an 80-mesh sieve, poured into a crucible after screening, and then placed in a box-type resistance furnace set at 1300°C for 3 hours to perform powder phase sintering, wherein the heating rate is 5°C / min below 1000°C and 2°C / min above 1000°C; after sintering, the temperature is cooled to room temperature at 100°C / h to obtain a chemical formula (Y 0.4 Er 0.6 )3(Al 0.95 Ca 0.05 )5O 12 powder material.
[0118] S3: The powder material obtained by sintering in step S2 is dried by ball milling for the third time, ground and screened, pressed into tablets and sintered to prepare a multi-element co-doped yttrium aluminum garnet ceramic material.
[0119] The chemical formula obtained by sintering step S2 is (Y 0.4 Er 0.6 )3(Al 0.95 Ca 0.05 )5O 12 The powder material is poured into a nylon ball mill and placed in a planetary ball mill, and ball milled for the third time at 150r / min for 24h. After ball milling, it is placed in an electric constant temperature blast drying oven at a constant temperature of 80℃ for 24h; then it is ground with an agate mortar and passed through a 200-mesh sieve. The sieved powder material is pre-pressed at 8MPa on a tablet press and the pressure is maintained for 50s; after the tableting is completed, the tablet is wrapped with plastic film, placed in a vacuum bag and evacuated, and cold isostatically pressed at 220MPa for 90s. The pressed block is sent to a resistance furnace and set at 1300℃ for 8h for secondary sintering, wherein the heating rate is 5℃ / min below 1000℃ and 2℃ / min above 1000℃; after sintering, the temperature is cooled to room temperature at 100℃ / h, and the chemical formula is finally obtained (Y 0.4 Er 0.6 )3(Al 0.95 Ca 0.05 )5O 12 Ceramic material.
[0120] Performance testing
[0121] (1) Thermal conductivity test
[0122] The (Y 0.4 Er 0.6 )3(Al 0.95 Ca 0.05 )5O 12 Thermal conductivity tests are performed on ceramic materials, such as Figure 10 As shown in Figure 2, as the temperature increases, the thermal conductivity decreases continuously; at 1100℃, (Y 0.4 Er 0.6 )3(Al 0.95 Ca 0.05 )5O 12 Ceramic materials have the lowest thermal conductivity, which is 1.36W / m·K.
[0123] (2) Thermal expansion performance test
[0124] The (Y 0.4 Er 0.6 )3(Al 0.95 Ca 0.05 )5O12 Ceramic materials are tested for thermal expansion properties, such as Figure 11 As shown, at 1200℃, (Y 0.4 Er 0.6 )3(Al 0.95 Ca 0.05 )5O 12 The thermal expansion coefficient of ceramic material is 8.3×10 -6 K -1 .
[0125] Example 5
[0126] In this embodiment, a solid-phase synthesis method is used to prepare a yttrium aluminum garnet thermal barrier coating material co-doped with the rare earth element Er and the metal element Mg. The specific preparation method includes the following steps:
[0127] S1: Preparation of nano-scale powder raw materials Y2O3, Er2O3, Al(OH)3, and MgO
[0128] 99.999wt% pure Y2O3 powder, 99.99wt% Er2O3 powder, analytically pure Al(OH)3 powder, 99.99wt% MgO powder, deionized water, and a polymethacrylamide dispersant were poured into a polyurethane ball mill for the first round of ball milling. The mass ratio of Y2O3 powder to water was 1:1.5; the mass ratio of Er2O3 powder to water was 1:1.5; the mass ratio of MgO powder to water was 1:1.5; and the mass ratio of Al(OH)3 powder to water was 1:4. The polyurethane ball mill was placed in a planetary ball mill and milled at 150 rpm for 24 hours. When ball-milling Y2O3 powder, Er2O3 powder and MgO powder, when their solid content is less than 40%, 4wt‰ of CE64 dispersant is added thereto; when ball-milling Al(OH)3 powder, when its solid content is less than 20%, 2wt% of CE64 dispersant is added thereto.
[0129] The slurry was then poured into a sand mill and sand-milled for 1 hour at speeds of 2300, 2500, and 2700 rpm, respectively. Simultaneously, a polymethacrylamide dispersant was added dropwise according to the appropriate proportions: 4 wt% of dispersant was added to the Y2O3, Er2O3, and MgO powders; and 2 wt% of dispersant was added to the Al(OH)3 powder. After sand-milling, the slurry was poured into a stainless steel tray and dried in an oven at 90°C for 24 hours to obtain a nanopowder with uniform particle size.
[0130] S2: Mixing of nano-scale powder raw materials, secondary ball milling and drying, grinding, screening and sintering to prepare multi-element co-doped yttrium aluminum garnet powder material
[0131] Y2O3, Er2O3, Al(OH)3, MgO nanopowders were mixed in a molar ratio of 6:9:47.5:2.5, and anhydrous ethanol was added as a dispersant. The mass ratio of the dispersant to the nanoparticle mixture was 2:1. Then the mixture was poured into a nylon ball mill and placed in a planetary ball mill for a second ball milling at 150r / min for 24h. After the ball milling was completed, the material was poured into a beaker, the beaker mouth was sealed with a film, a few small holes were poked with a knife, and the mixture was placed in an electric constant temperature blast drying oven at a constant temperature of 80°C for 24h; the dried material was ground with an agate mortar and passed through an 80-mesh sieve. After screening, the material was poured into a crucible and then placed in a box-type resistance furnace set at 1300°C for 3h for powder phase sintering, wherein the heating rate was 5°C / min below 1000°C and 2°C / min above 1000°C; after sintering, the temperature was cooled to room temperature at 100°C / h to obtain a chemical formula (Y 0.4 Er 0.6 )3(Al 0.95 Mg 0.05 )5O 12 powder material.
[0132] S3: The powder material obtained by sintering in step S2 is dried by ball milling for the third time, ground and screened, pressed into tablets and sintered to prepare a multi-element co-doped yttrium aluminum garnet ceramic material.
[0133] The powder material obtained by sintering step S2 is poured into a nylon ball mill and placed in a planetary ball mill, and ball milled for the third time at 150r / min for 24h. After ball milling, it is placed in an electric constant temperature blast drying oven at a constant temperature of 80℃ for 24h; then ground with an agate mortar and passed through a 200-mesh sieve, and the sieved powder material is pre-pressed at 8MPa on a tablet press, and the pressure is maintained for 50s; after tableting, the tablet is wrapped with plastic film, placed in a vacuum bag and evacuated, and cold isostatically pressed at 220MPa, and the pressure is maintained for 90s. The pressed block is sent to a resistance furnace and set at 1300℃ for 8h for secondary sintering, wherein the heating rate is 5℃ / min below 1000℃ and 2℃ / min above 1000℃; after sintering, it is cooled to room temperature at 100℃ / h, and the chemical formula is finally obtained. 0.4 Er 0.6 )3(Al 0.95 Mg 0.05 )5O 12 of ceramic materials.
[0134] Performance testing
[0135] (1) Thermal conductivity test
[0136] The (Y 0.4 Er 0.6 )3(Al 0.95 Mg 0.05 )5O12 Thermal conductivity tests are performed on ceramic materials, such as Figure 10 As shown in Figure 2, as the temperature increases, the thermal conductivity decreases continuously; at 1100℃, (Y 0.4 Er 0.6 )3(Al 0.95 Mg 0.05 )5O 12 Ceramic materials have the lowest thermal conductivity, which is 1.38W / m·K.
[0137] (2) Thermal expansion performance test
[0138] The (Y 0.4 Er 0.6 )3(Al 0.95 Mg 0.05 )5O 12 Ceramic materials are tested for thermal expansion properties, such as Figure 11 As shown, at 1200℃, (Y 0.4 Er 0.6 )3(Al 0.95 Mg 0.05 )5O 12 The thermal expansion coefficient of ceramic material is 7.7×10 -6 K -1 .
[0139] In summary, the present invention adopts a ceramic preparation method that combines "ball milling + sand milling + secondary ball milling + grinding + sintering + tertiary ball milling + grinding + sintering". The nanopowder obtained by ball milling and sand milling the raw materials is subjected to secondary ball milling, grinding and screening, and phase sintering, and then ball milling, grinding and screening, and ceramic sintering are performed three times. The prepared ceramic material has higher phase purity, smaller grain size, more uniform component distribution, and the doped ions are more easily fully dissolved in the YAG lattice. This is because the particle size of the raw material powder is more uniform and fine after ball milling and sand milling, which is more conducive to powder phase formation; after the powder is ball milled twice, ground and screened, and phase sintered, the third ball milling, grinding and screening, and ceramic sintering are performed, so that the particle size of the sintered ceramic grains is further refined and uniform, the phase formation is more complete, and the mixing uniformity is better. The preparation method of the present invention has the advantages of simple operation, low cost, easy control, high reliability, and suitability for large-scale industrial production.
[0140] The present invention adopts material design, utilizes rare earth elements to dope the Y position of yttrium aluminum garnet, and metal elements to dope the Al position of yttrium aluminum garnet, and prepares a multi-element co-doped yttrium aluminum garnet thermal barrier coating material according to the method of the present invention. The multi-element co-doped yttrium aluminum garnet thermal barrier coating material has a single YAG phase, a stable high-temperature phase structure, a precise proportion of doped ions, controllable doped ion occupancy, and low oxygen ion transmittance. While maintaining low thermal conductivity, the thermal expansion coefficient is significantly improved. The thermal barrier coating material is a candidate material with excellent comprehensive thermophysical properties, which has broad application prospects in aerospace, shipbuilding, nuclear industry, automobile and other fields.
[0141] The multi-element co-doped ceramic material produced by this invention is primarily used in the preparation of protective coatings for hot-end components in the aerospace, shipbuilding, nuclear, and automotive industries, including engine combustion chambers, rocket nozzles, civilian internal combustion engines, supercharged turbines, and heat treatment annealing furnaces. Through techniques such as plasma spraying, laser cladding, and physical vapor deposition, the ceramic material is composited with a high-temperature resistant metal or superalloy in the form of a coating. This provides thermal insulation for the substrate material, lowering the substrate temperature and enabling components made from it (such as engine turbine blades) to operate at high temperatures. This improves the efficiency and operating temperature of turbine engines, extending their service life. This material has broad application prospects and a huge market demand, potentially bringing significant economic and social benefits.
[0142] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications to the above embodiments are possible. Any simple modifications, equivalent variations, and modifications made in accordance with the claims and description of the present invention are within the scope of protection of the patent claims. Any content not described in detail in this patent application constitutes conventional technology.
Claims
1. A multi-element co-doped yttrium aluminum garnet thermal barrier coating material, characterized in that: The multi-element co-doped yttrium aluminum garnet thermal barrier coating material is a single-phase garnet structure, which is prepared by doping the Y position of yttrium aluminum garnet with a rare earth element and doping the Al position of yttrium aluminum garnet with a metal element; the chemical formula of the multi-element co-doped yttrium aluminum garnet thermal barrier coating material is (Y 1-x Ln x )3(Al 1- y B y )5O 12 , where Ln is Er; the doping variable satisfies one of the following conditions: (a) When Ln is Er and B is Fe, the doping variables satisfy x=0.6, 0.4≤y≤0.8; (b) When Ln is Er and B is Mn, the doping variables satisfy x=0.6, 0.04≤y≤0.1; (c) When Ln is Er and B is Ti, the doping variables satisfy x=0.6, 0.04≤y≤0.
1.
2. A method for preparing the multi-element co-doped yttrium aluminum garnet thermal barrier coating material according to claim 1, characterized in that: The steps include: S1: respectively subjecting Y2O3 powder, Al(OH)3 powder, rare earth element compound powder and metal element compound powder to a first ball milling and sand milling until their particle sizes reach nanometer level, and drying to obtain nanometer level powders of Y2O3, Al(OH)3, rare earth element compound and metal element compound; S2: ball-milling the nano-sized powders Y2O3, Al(OH)3, rare earth element compounds and metal element compounds for a second time, drying them, grinding and screening them, and then sintering the powders to obtain a powder material of yttrium aluminum garnet co-doped with rare earth elements and metal elements; S3: The powder material of yttrium aluminum garnet co-doped with rare earth elements and metal elements obtained in step S2 is ball-milled for the third time, dried, ground and sieved, the sieved powder is pressed into a block, and the block is sintered to obtain a multi-element co-doped yttrium aluminum garnet thermal barrier coating material.
3. The method for preparing the multi-element co-doped yttrium aluminum garnet thermal barrier coating material according to claim 2, characterized in that: The rare earth element compound is Er2O3; the metal element compound is one of TiO2, Fe2O3 and MnCO3.
4. The method for preparing the multi-element co-doped yttrium aluminum garnet thermal barrier coating material according to claim 2, characterized in that: The sieving in step S2 is through an 80-mesh sieve, and the sieving in step S3 is through a 200-mesh sieve.
5. The method for preparing the multi-element co-doped yttrium aluminum garnet thermal barrier coating material according to claim 2, characterized in that: The pressing and forming into a block in step S3 comprises the following steps: The sieved powder is pre-pressed at 8 MPa and maintained at the pressure for 50 to 60 seconds, and is cold isostatically pressed at 220 MPa under vacuum conditions and maintained at the pressure for 90 to 180 seconds to obtain a block.
6. The method for preparing the multi-element co-doped yttrium aluminum garnet thermal barrier coating material according to claim 2, characterized in that: The temperature conditions for the powder phase sintering in step S2 are as follows: heating to 1000°C at 5°C / min, then heating to 1300°C at 2°C / min, keeping at 1000°C to 1600°C for 3 to 10 hours, and then cooling to room temperature at 100°C / h; The temperature conditions for block sintering in step S3 are as follows: heating to 1000°C at 5°C / min, then heating to 1300°C at 2°C / min, keeping at 1000°C-1600°C for 3-10h, and then cooling to room temperature at 100°C / h.
7. The method for preparing the multi-element co-doped yttrium aluminum garnet thermal barrier coating material according to claim 2, characterized in that: The preparation method of the nano-powder Y2O3, Al(OH)3, rare earth element compound and metal element compound in step S1 is as follows: Water and polymethacrylate dispersant were added to Y2O3 powder, Al(OH)3 powder, rare earth element compound powder and metal element compound powder respectively, and the powders were ball-milled at 150 r / min for 24 h, and then sand-milled at 2300 r / min, 2500 r / min and 2700 r / min for 1 h respectively. After drying, Y2O3 nano-powder, Al(OH)3 nano-powder, rare earth oxide nano-powder and metal oxide nano-powder were obtained respectively.
8. The method for preparing the multi-element co-doped yttrium aluminum garnet thermal barrier coating material according to claim 7, characterized in that: During the ball milling process, the weight ratio of the Y2O3 powder, the rare earth element compound powder and water is 1:1.
5. When the solid content of the Y2O3 powder and the rare earth element compound powder is less than 40%, 4wt‰ of polymethacrylate dispersant is added to the Y2O3 powder and the rare earth element compound powder respectively; the weight ratio of the Al(OH)3 powder, the metal element compound powder and water is 1:
4. When the solid content of the Al(OH)3 powder is less than 20%, 2wt% of polymethacrylate dispersant is added to the Al(OH)3 powder; when the solid content of the metal element compound powder is less than 20% to 30%, 1 to 2wt% of polymethacrylate dispersant is added to the metal element compound powder; During the sand grinding process, when the Y2O3 powder, Al(OH)3 powder, rare earth element compound powder and metal element compound powder are viscous, 1 g of polymethacrylate dispersant is added to the powder; when a large number of bubbles appear in the powder, 2 drops of n-octanol are dropped into the powder.